2014
DOI: 10.1002/acn3.34
|View full text |Cite
|
Sign up to set email alerts
|

Febrile seizure recurrence reduced by intermittent oral levetiracetam

Abstract: ObjectiveFebrile seizure (FS) is the most common form of childhood seizure disorders. FS is perhaps one of the most frequent causes of admittance to pediatric emergency wards worldwide. We aimed to identify a new, safe, and effective therapy for preventing FS recurrence.MethodsA total of 115 children with a history of two or more episodes of FS were randomly assigned to levetiracetam (LEV) and control (LEV/control ratio = 2:1) groups. At the onset of fever, LEV group was orally administered with a dose of 15–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The present findings demonstrated that ~51% of the children had undergone FS recurrences within 12 months from their first FS. These findings correlate with the data collected in previous reports ( 17 , 21 , 22 ). In our study, it was demonstrated that intermittent oral LEV effectively prevented FS recurrence in the LEV group (15.6%; 7/45) as compared with the control group (51.0%; 26/51).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present findings demonstrated that ~51% of the children had undergone FS recurrences within 12 months from their first FS. These findings correlate with the data collected in previous reports ( 17 , 21 , 22 ). In our study, it was demonstrated that intermittent oral LEV effectively prevented FS recurrence in the LEV group (15.6%; 7/45) as compared with the control group (51.0%; 26/51).…”
Section: Discussionsupporting
confidence: 93%
“…In several animal models, LEV has been shown to be a highly effective antiepileptic drug against partial and generalized seizures ( 26 , 27 ). A randomized clinical trial by Hu et al ( 17 ) demonstrated a significant reduction in FS recurrence with intermittent oral LEV. In the chronic phase of acute encephalitis with refractory, repetitive partial seizures, administration of LEV (750–1,500 mg/kg) has been shown to reduce seizure frequency by >75% for 5 to 18 months ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Intermittent oral levetiracetam was found in one study to be efficacious in preventing febrile seizure recurrence with minimal side effects. 56 A recent systematic review of prophylactic drug therapy in children with febrile seizures found reduced recurrence rates in children with continuous phenobarbitone (significant reduction at 6, 12, and 24 months, but not at 18 or 72 months of follow-up) or intermittent diazepam (significant reduction at 12, 24, 36, and 48 months but not at 60-72 months). Both drugs produced mild-to-moderate adverse side effects in up to 30% of children.…”
Section: Use Of Antipyretics and Antiepileptic Medicationsmentioning
confidence: 99%
“…In more tests, however, LEV was reported to disrupt sleep, causing an increase in N2 sleep and a decrease in total sleep time, deep NREM sleep, and REM sleep [ 150 , 151 ]. Most studies pointed to the possibility of daytime drowsiness [ 152 ].…”
Section: Sleep and Anticonvulsant Therapymentioning
confidence: 99%